2021
DOI: 10.1158/1078-0432.ccr-21-0047
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Alpelisib in Combination with Trastuzumab and LJM716 in Patients with PIK3CA-Mutated HER2-Positive Metastatic Breast Cancer

Abstract: Purpose: Activating mutations in PIK3CA promote resistance to HER2-targeted therapy in breast cancer; however, inhibition of PI3K alone leads to escape via feedback upregulation of HER3. Combined inhibition of HER2, HER3, and PI3K overcomes this mechanism preclinically. Patients and Methods: This phase I study investigated the MTD of alpelisib given in combination with trastuzumab and LJM716 (a HER3-targeted antibody) in pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The NRG-HER3-HER2 axis has been strongly implicated in HER2+ breast cancer relapse [10,17,27,30,32,61], and preclinical studies have shown that pertuzumab and LJM716 (HER3-inactivating mAb) significantly reduce the outgrowth of experimental HER2+BM [27]. Further clinical development of LJM716 is underway [62,63], though it is unclear if planned clinical trials will assess intracranial progression as a specific endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…The NRG-HER3-HER2 axis has been strongly implicated in HER2+ breast cancer relapse [10,17,27,30,32,61], and preclinical studies have shown that pertuzumab and LJM716 (HER3-inactivating mAb) significantly reduce the outgrowth of experimental HER2+BM [27]. Further clinical development of LJM716 is underway [62,63], though it is unclear if planned clinical trials will assess intracranial progression as a specific endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Alpelisib and taselisib are PI3K isoform-specific inhibitors that were also evaluated in HR+ BC [ 235 , 236 , 238 , 253 , 254 ]. A phase I study evaluated alpelisib in combination with trastuzumab and LJM716 (a HER3-targeted antibody) in patients with PI3KCA mutant HER2+ metastatic BC [ 272 ]. Unfortunately, the results of this study were limited by high gastrointestinal toxicity.…”
Section: New Strategies and Challenges For Breast Cancer Treatmentmentioning
confidence: 99%
“…25,26 Twenty and twenty-eight percent of the patients with PIK3CA-mutated HER2-positive and hormone receptor-positive, HER2-negative metastatic breast cancer, respectively, developed high-grade hyperglycemia when treated with alpelisib in recent trials. 27,28 In most PAMi studies, hyperglycemia is controlled with metformin less frequently with a second oral agent or insulin and rarely with chemotherapy discontinuation. 3,[29][30][31][32] In 2012, an algorithm for screening and management of DM in PAMi-treated patients was proposed.…”
Section: Pi3k-akt Pathway In Glucose Homeostasismentioning
confidence: 99%
“…25,26 Twenty and twenty-eight percent of the patients with PIK3CA -mutated HER2-positive and hormone receptor–positive, HER2-negative metastatic breast cancer, respectively, developed high-grade hyperglycemia when treated with alpelisib in recent trials. 27,28…”
Section: Pami-induced Hyperglycemia and Managementmentioning
confidence: 99%